Collaboration Leads to Enhanced Curriculum - Valerius, J.; Mohan, V.; Doctor, D.; Hersh, W. (Applied Clinical Informatics, 2015)
Background: In 2007, we initiated a health information management (HIM) track of our biomedical informatics graduate program, and subsequent ongoing program assessment revealed a confluence of topics and courses within HIM and clinical informatics (CI) tracks. We completed a thorough comparative analysis of competencies derived from AMIA, AHIMA, and CAHIIM. Coupled with the need to streamline course offerings, the process, described in this paper allowed new opportunities for faculty collaboration, resulted in the creation of a model assessment for best practice in courses, and led to new avenues of growth within the program.Objective: The objective of the case study is to provide others in the informatics educational community with a model for analysis of curriculum in order to improve quality of student learning.Methods: We describe a case study where an academic informatics program realigned its course offerings to better reflect the HIM of today, and prepare for challenges of the future. Visionary leadership, intra-departmental self-analysis and alignment of the curriculum through defined mapping process reduced overlap within the CI and HIM tracks. Teaching within courses was optimized through the work of core faculty collaboration.Results: The analysis of curriculum resulted in reduction of overlap within course curriculum. This allowed for additional and new course content to be added to existing courses.Conclusions: Leadership fostered an environment where top-down as well as bottom-up collaborative assessment activities resulted in a model to consolidate learning and reduce unnecessary duplication within courses. A focus on curriculum integration, emphasis on course alignment and strategic consolidation of course content raised the quality of informatics education provided to students. Faculty synergy was an essential component of this redesign process. Continuous quality improvement strategy included an ongoing alignment of curriculum and competencies through a comparative analysis approach. Through these efforts, new innovation was possible.Citation: Valerius J, Mohan V, Doctor D, Hersh W. Collaboration leads to enhanced curriculum. Appl Clin Inf 2015; 6: 200–209http://dx.doi.org/10.4338/ACI-2014-10-CR-0086
Keywords: Informatics; information technology; health information management; education; collaboration; curriculum enhancement; certification; clinical informatics; professional training; education training and education requirements; workforce education; organizational change management; culture; workflows and human interactions; socio-technical aspects of information technology